2019
DOI: 10.3390/ijerph16122113
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Leptospira Infection in Rodents from Bangladesh

Abstract: Worldwide, Leptospira infection poses an increasing public health problem. In 2008, leptospirosis was recognised as a re-emerging zoonosis of global importance with South-East Asia being one of the most significant centres of the disease. Rodents are thought to be the most important host for a variety of Leptospira serovars. Because Bangladesh offers a suitable humid climate for the survival of these pathogenic bacteria, the presence of rodents could be a serious risk for human infection, especially in peri-ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 75 publications
2
12
1
3
Order By: Relevance
“…Los animales de producción y de compañía juegan un papel muy importante en la epidemiología de la enfermedad, ya que pueden actuar como hospederos de Leptospira spp. Sin embargo, los roedores son uno de los reservorios más importantes para que esta bacteria permanezca en el medio ambiente (4). La principal vía de trasmisión a los humanos es a través del contacto con tejidos u orina de animales infectados, así como barro o agua contaminada con la orina de los animales infectados (5).…”
Section: Introductionunclassified
“…Los animales de producción y de compañía juegan un papel muy importante en la epidemiología de la enfermedad, ya que pueden actuar como hospederos de Leptospira spp. Sin embargo, los roedores son uno de los reservorios más importantes para que esta bacteria permanezca en el medio ambiente (4). La principal vía de trasmisión a los humanos es a través del contacto con tejidos u orina de animales infectados, así como barro o agua contaminada con la orina de los animales infectados (5).…”
Section: Introductionunclassified
“…L. interrogans and L. kirschneri are two of the most common leptospiral species present in rodents in Europe [32,33]. L. interrogans have also been reported from rodents in studies from Puerto Rico, Bangladesh and Thailand [21,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The infection rates of Leptospira in wild and domesticated animals are varied in different places around the world. In Bangladesh, 13.1% (61/465) of trapped rodents were infected with pathogenic Leptospira (Krijger et al 2019); in Cambodia, the infection rate of Leptospira in rodents was 11.1% (n = 642) (Ivanova et al 2012); in Malaysia, the infection rate in rodents was 11.0% (n = 357) (Benacer et al 2016); in China, it was 56.7% (34/60) in bats (Zhao et al 2019) and 4.4% (3/69) in flying squirrels (Xiao et al 2019). Previously Leptospira has been isolated from hedgehogs in several European countries, including France, Italy, The Netherlands, and Scotland, Israel, and New Zealand (Vander Hoeden 1958, Broom and Coghlan 1960, Babudieri and Farina 1964, Wolff and Bohlander 1965, Brockie and Till 1977, Ayral et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the infection does not seem to harm adult hedgehogs as even animals with active infections appeared to be in good health, consistent with the report that Leptospira serovars usually do not cause disease in their natural host (Ko et al 2009). Hedgehogs are considered to be a tonic in traditional Chinese medicine, thus this species is frequently taken from the wild and eaten across Central China, and people may be infected in the process of capturing or slaughtering hedgehogs (Krijger et al 2019). Therefore, increased awareness and protective measures are needed to prevent Leptospira infections.…”
Section: Discussionmentioning
confidence: 99%